Clinical Practice Guideline for the Medical Management of Perianal Fistulizing Crohn's Disease: The Toronto Consensus. Issue 1 (6th August 2018) - Steinhart, A Hillary; Panaccione, Remo; Targownik, Laura; Bressler, Brian; Khanna, Reena; Marshall, John K; Afif, Waqqas; Bernstein, Charles N; Bitton, Alain; Borgaonkar, Mark; Chauhan, Usha; Halloran, Brendan; et al.
Abstract: Background: Fistulas occur in about 25% of patients with Crohn's disease (CD) and can be difficult to treat. The aim of this consensus was to provide guidance for the management of patients with perianal fistulizing CD. Methods: A systematic literature search identified studies on the management of fistulizing CD. The quality of evidence and strength of recommendations were rated according to the Grading of Recommendation Assessment, Development and Evaluation (GRADE) approach. Statements were developed through an iterative online platform using a modified Delphi process, then finalized, and voted on by a group of specialists. Results: The quality of evidence for treatment of fistulizing CD was generally of very low quality, and because of the scarcity of good randomized controlled trials (RCTs), these consensus statements generally provide conditional suggestions (5 of 7 statements). Imaging and surgical consultations were recommended in the initial assessment of patients with active fistulizing CD, particularly those with complicated disease. Antibiotic therapy is useful for initial symptom control. Antitumor necrosis factor (anti-TNF) therapy was recommended to induce symptomatic response, and continued use was suggested to achieve and maintain complete remission. The use of concomitant immunosuppressant therapies may be useful to optimize pharmacokinetic parameters when initiating anti-TNF therapy. When there has been an inadequate symptomatic response to medical management strategies, surgical therapy may provide effective fistula healing for some patients. Conclusions: Optimal management of perianal fistulizing CD requires a collaborative effort between gastroenterologists and surgeons and may include the evidence-based use of existing therapies, as well as surgical assessments and interventions when needed.